Medicinal Plants Used for Hepatoprotective Activity: A Focus on Picrorhiza kurroa Royle ex Benth. and Piper longum L. - Garg, Shubham; Savanur, Prasanna V; Gupta, Ramji; Sharma, Nitya (International Research Journal of Ayurveda & Yoga, 2024)
The liver is vital for numerous physiological functions, including metabolism, detoxification, and immune regulation. Hepatic diseases, which may arise from infections, drugs, alcohol, toxins, and metabolic disorders, represent a major global health challenge. Traditional medicine has provided a wealth of plant-based remedies for liver protection. This review aims to evaluate and compare the hepatoprotective activity of several medicinal plants in rats, with a focus on Picrorhiza kurroa, Piper longum, Silybum marianum, and Andrographis paniculata. By examining their phytochemical composition, mechanisms of action, and the experimental evidence from rat models, we present a comprehensive understanding of their hepatoprotective potential and therapeutic value. The liver is a highly regenerative organ but is prone to damage from various insults, including chemicals (e.g., CCl₄), drugs (e.g., acetaminophen), infections (e.g., hepatitis), and metabolic disturbances (e.g., fatty liver disease). Traditional medicinal plants have been used across cultures for centuries to support liver function and treat liver-related ailments. [1] This review focuses on evaluating medicinal plants with demonstrated hepatoprotective effects in experimental rat models. Rats are commonly used to study liver damage